Incidence and Predictors of Dyspnea on Exertion in a Prospective Cohort of Patients With Rheumatoid Arthritis. Issue 1 (15th March 2019) - Sparks, Jeffrey A.; Doyle, Tracy J.; He, Xintong; Pan, Beatrice; Iannaccone, Christine; Frits, Michelle L.; Dellaripa, Paul F.; Rosas, Ivan O.; Lu, Bing; Weinblatt, Michael E.; Shadick, Nancy A.; Karlson, Elizabeth W.
Abstract : Objective: To investigate the incidence and predictors of dyspnea on exertion among subjects with rheumatoid arthritis (RA). Methods: We investigated dyspnea on exertion using a prospective cohort, the Brigham RA Sequential Study (BRASS). Clinically significant dyspnea on exertion was defined as a score of ≥ 3 (unable to ambulate without breathlessness or worse) on the validated Medical Research Council (MRC) scale (range 0‐5). We analyzed subjects with MRC score < 3 at BRASS baseline and at ≥ 1 year of follow‐up. The MRC scale was administered annually. We determined the incidence rate (IR) of dyspnea on exertion. We used Cox regression to estimate the hazard ration (HR) for dyspnea on exertion occurring one year after potential predictors were assessed. Results: We analyzed 829 subjects with RA and no clinically significant dyspnea on exertion during a mean follow‐up period of 3.0 years (SD 1.9). At baseline, mean age was 55.7 years (SD 13.6), 82.4% of subjects were female, and median RA duration was 8 years. During follow‐up, 112 subjects (13.5%) developed incident dyspnea on exertion during 2476 person‐years of follow‐up (incidence rate 45.2 per 1000 person‐years). Independent predictors of incident dyspnea on exertion were older age (HR 1.03 per year, 95% CI, 1.01‐1.04), female sex (HR 2.22, 95% CI, 1.14‐4.29), mild dyspnea (HR 2.62, 95% CI, 1.60‐4.28), and worsened Multi‐Dimensional Health Assessment Questionnaire score (HR 2.36 per unit, 95% CI, 1.54‐3.60). Methotrexate use, RA disease activity, and seropositivity were not associated with incident dyspnea on exertion after accounting for other dyspnea risk factors. Conclusion: Dyspnea on exertion occurred commonly in patients with RA. Older women with impaired physical function were especially vulnerable to developing dyspnea on exertion.